Self-assessment tool for evaluating periodontal conditions - Rani, Haslina; Mohd-Dom, Tuti Ningseh; Mohd-Said, Shahida; Johari, Nur Azwani (UI Scholars Hub, 2020)
Background: The global prevalence of periodontal disease is steadily rising. Early detection through the active screening of potential patients is important because periodontal disease leads to high disease, clinical, and economic burdens. The aim of this study is to develop a simple periodontal assessment tool for the Malay-speaking population; this tool is referred to in this work as MyGusi. Methods: Translation and back-translation of a self-assessment tool containing 10 items related to periodontal health conditions and risk behaviors were conducted by three bilingual translators. Nine periodontists were selected to determine the content validity of the tool. After pre-testing for face validity, MyGusi was distributed to patients attending dental clinics in a public university in Kuala Lumpur. The Basic Periodontal Examination (BPE) of each patient was obtained from their dental records. Results: The scale-content validity index of MyGusi was 0.92, which indicates good validity. Cronbach's alpha was calculated to assess the internal consistency of the tool, and the value obtained (0.72) indicated acceptable reliability. The mean total MyGusi and BPE scores were positively correlated at 0.488 (p < 0.001). Conclusion: MyGusi has good content validity and is positively correlated with BPE, an established periodontal screening tool.